C3d‐positive donor‐specific antibodies have a role in pretransplant risk stratification of cross‐match‐positive HLA‐incompatible renal transplantation: United Kingdom multicentre study. (25th June 2020) - Babu, Adarsh; Khovanova, Natasha; Shaw, Olivia; Griffin, Sian; Briggs, David; Krishnan, Nithya S.; Fletcher, Simon; Imray, Christopher; Seitz, Adrienne; Baker, Richard; Wellberry‐Smith, Matthew; Clarke, Brendan; et al.
Abstract: Anti‐HLA‐antibody characteristics aid to risk‐stratify patients and improve long‐term renal graft outcomes. Complement activation by donor‐specific antibody (DSA) is an important characteristic that may determine renal allograft outcome. There is heterogeneity in graft outcomes within the moderate to high immunological risk cases (cross‐match‐positive). We explored the role of C3d‐positive DSAs in sub‐stratification of cross‐match‐positive cases and relate to the graft outcomes. We investigated 139 cross‐match‐positive living‐donor renal transplant recipients from four transplant centres in the United Kingdom. C3d assay was performed on serum samples obtained at pretreatment (predesensitization) and Day 14 post‐transplant. C3d‐positive DSAs were found in 52 (37%) patients at pretreatment and in 37 (27%) patients at Day 14 post‐transplant. Median follow‐up of patients was 48 months (IQR 20.47–77.57). In the multivariable analysis, pretreatment C3d‐positive DSA was independently associated with reduced overall graft survival, the hazard ratio of 3.29 (95% CI 1.37–7.86). The relative risk of death‐censored five‐year graft failure was 2.83 (95% CI 1.56–5.13). Patients with both pretreatment and Day 14 C3d‐positive DSAs had the worst five‐year graft survival at 45.5% compared with 87.2% in both pretreatment and Day 14 C3d‐negative DSA patients with the relative risk of death‐censored five‐year graft failure was 4.26 (95% CI 1.79, 10.09). In this multicentre study, we have demonstrated for the first time the utility of C3d analysis as a distinctive biomarker to sub‐stratify the risk of poor graft outcome in cross‐match‐positive living‐donor renal transplantation.